2019
DOI: 10.3390/pharmaceutics11070335
|View full text |Cite
|
Sign up to set email alerts
|

17-α Hydroxyprogesterone Nanoemulsifying Preconcentrate-Loaded Vaginal Tablet: A Novel Non-Invasive Approach for the Prevention of Preterm Birth

Abstract: Preterm birth (PTB) is a major cause of infant mortality in the United States and around the globe. Makena®—once-a-week intramuscular injection of 17-α Hydroxyprogesterone caproate (17P)—is the only FDA approved treatment for the prevention of PTB. Invasive delivery of 17P requires hospitalization and expert personnel for injection. Vaginal delivery of 17P would be preferable, because of high patient compliance, reduced systemic exposure, fewer side effects, and no need for hospitalization. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…For the preparation of vaginal microemulsions and SEDDS systems, fatty acid derivatives such as Captex ® 300 (ABITEC, Columbus, USA), Capryol ® 90 (Gattefossé, Saint-Priest, France), glycerol monolaurate and oleic acid have been used as the oil phase components [ 76 , 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. These excipients exhibited high solubility of lipophilic compounds, e.g., clotrimazole or tetrahydrocurcumin and were also selected due to their additional properties, such as strong microemulsifying properties (Capryol ® 90, Gattefossé, Saint-Priest, France), anti-HIV activity (glycerol monolaurate) and low toxicity (Captex ® 300, ABITEC, Columbus, USA) [ 76 , 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Cetyl palmitate and other diesters and triesters of fatty acids, e.g., Labrasol ® (Gattefossé, Saint-Priest, France), triglycerides of medium-length fatty acids have also been proposed in the preparation of vaginal emulsions [ 76 , 79 , 82 , 83 , 84 , 85 , 86 , 89 , 90 , 91 , 92 ].…”
Section: Technological Aspects Of Vaginal Formulations Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For the preparation of vaginal microemulsions and SEDDS systems, fatty acid derivatives such as Captex ® 300 (ABITEC, Columbus, USA), Capryol ® 90 (Gattefossé, Saint-Priest, France), glycerol monolaurate and oleic acid have been used as the oil phase components [ 76 , 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. These excipients exhibited high solubility of lipophilic compounds, e.g., clotrimazole or tetrahydrocurcumin and were also selected due to their additional properties, such as strong microemulsifying properties (Capryol ® 90, Gattefossé, Saint-Priest, France), anti-HIV activity (glycerol monolaurate) and low toxicity (Captex ® 300, ABITEC, Columbus, USA) [ 76 , 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Cetyl palmitate and other diesters and triesters of fatty acids, e.g., Labrasol ® (Gattefossé, Saint-Priest, France), triglycerides of medium-length fatty acids have also been proposed in the preparation of vaginal emulsions [ 76 , 79 , 82 , 83 , 84 , 85 , 86 , 89 , 90 , 91 , 92 ].…”
Section: Technological Aspects Of Vaginal Formulations Developmentmentioning
confidence: 99%
“…Optical microscopy is most frequently used for emulsions with droplet sizes in the micrometer range, i.e., macroemulsions, as it only allows the observation of particles larger than 200 nm [ 80 , 81 , 89 , 102 , 104 , 130 ]. The most commonly used method to determine the dispersed phase droplet size of micro- and nanoemulsion-based vaginal dosage forms is the dynamic light scattering (DLS) method, also known as photon correlation spectroscopy, that enables the measurement of droplet sizes in the range from 1 nm to 6 µm [ 74 , 75 , 76 , 77 , 78 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 98 , 99 , 103 , 105 ]. The accuracy of the obtained results depends on the measurement method and sample preparation, the sample dilution in particular [ 130 ].…”
Section: Technological Aspects Of Vaginal Formulations Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports based on these formulations have proven possible enhancement of BA of different drugs. [16][17][18][19][20] Nano-emulsions are emerging as very useful to improve performance of various biomedical systems based on drug delivery, food, cosmetics and pharmaceuticals because of their small size and useful properties such as high surface area per unit volume, robust dilution stability, optical transparency and tunable rheology. 21 Due to small droplet size, nano-emulsions possess stability against sedimentation or creaming with Ostwald ripening that is the main mechanism of nano-emulsion breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…The excipients contained in the SNEDDS tend to facilitate bioavailability of the drugs not merely by improving drug solubility and permeability but by circumventing the metabolism by liver microsomes and inhibiting P-gp efflux, along with the ability to facilitate lymphatic drug absorption. Several literature studies on various self-emulsifying formulations have reported potential improvement in the bioavailability of various drugs (Kalantari et al, 2017;Alhasani et al, 2019;Patki et al, 2019;Alsk€ ar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%